As armas do senhor destroem a casa grande?: diálogos entre assessoria jurídica popular no Brasil e advocacia de interesse público na África do Sul - Thaís Lopes Santana Isaías (2023)
This research proposes to analyse practices of grassroots lawyering in Brazil and public interest lawyering in South Africa regarding conflicts that involve struggles for housing and land. I intend to do that from a feminist, anti-racist and decolonial perspective, and, more specifically, adopting “escrevivência” (writing as you experience it) and border thinking as theoretical approaches. The question driving this research is whether it is possible to establish a dialogue between experiences of grassroots lawyering and public interest lawyering and, if so, on what terms, and what the approximation between them can teach us about lawmaking in the global south. The hypothesis is that these experiences converge because both of them exist in the midst of racist, patriarchal, and classist structural contexts, marked by colonialism, as well because they are immersed in histories of intense grassroots struggles for survival and human rights. At the same time, they present considerable divergences when unfolding these structural aspects and struggles. Thus, the dialogue between grassroots lawyering and public interest lawyering is possible, but depends on establishing conditions of mutual understanding and considerations based on the simultaneous perception of differences and similarities. This requires both a look at our histories and surroundings, as well as announcing our positions, openness and fluidity of references and concepts. By doing so, it might be possible to extract important shared elements to build decolonial, antiracist and feminist perspectives of the law in the south, perspectives which are always unstable, uncertain and limited.